Community Outbreak Moderates the Association Between COVID-19-Related Behaviors and COVID-19 Fear Among Older People: A One-Year Longitudinal Study in Taiwan - Kuo, Yi-Jie; Chen, Yu-Pin; Wang, Hsiao-Wen; Liu, Chieh-hsiu; Strong, Carol; Saffari, Mohsen; Ko, Nai-Ying; Lin, Chung-Ying; Griffiths, Mark D. (Frontiers in Medicine, 2021)
Although health behavior theories indicate that fear is effective in activating preventive behaviors, whether COVID-19 severity moderates the association between fear of COVID-19 and preventive behaviors remains unclear. The present study investigated the association between the fear of COVID-19 and preventive behaviors during the COVID-19 community outbreak of two severity levels in Taiwan. We obtained data regarding the fear of COVID-19 and practice of preventive behaviors from 139 older people (mean age = 71.73 years; 30.2% men) through in-person interviews during a mild outbreak period (baseline assessment). Data from 126 of the 139 participants were obtained again through a telephone interview during a severe outbreak period (follow-up assessment). A significant increase in the fear of COVID-19 (d = 0.39, p < .001) and a decrease in preventive behaviors (d = 0.63, p < .001) were found in the follow-up assessment. The association between fear and preventive behaviors was not significant in the baseline (r = −.07, p > .05) but became significant in the follow-up assessment (r = .32, p < .001). The severity of a COVID-19 outbreak may alter older people’s psychological status and related behaviors.